Haemophagocytic lymphohistiocytosis following a COVID-19 infection: case report - Soldera, Jonathan; Bosi, Guilherme Rasia (The Journal of Infection in Developing Countries, 2023)
The case of a 57-year-old male patient with jaundice, high-grade fever, and upper abdominal pain who was recovering from a mild coronavirus disease-19 (COVID-19) infection is reported. Laboratory analysis showed liver injury with high levels of AST and ALT, as well as an elevated serum ferritin level. The patient underwent a bone marrow biopsy which showed features of hemophagocytic lymphohistiocytosis (HLH), a systemic syndrome caused by immune activation. The patient was successfully treated with etoposide and dexamethasone and kept on maintenance therapy with cyclosporine, with resolution of the HLH. The discussion highlights that COVID-19 infection may cause liver injury, and in severe cases, patients may develop HLH as a cause for liver injury. The incidence of HLH in adults with severe COVID-19 infection is estimated to be lower than 5%. The association between HLH and COVID-19 infection has been studied due to immunological hyperactivation. Signs such as persistent high fever, hepatosplenomegaly, and progressive pancytopenia should raise suspicion for the diagnosis of overlapping HLH. A specific approach using steroids and etoposide, followed by maintenance therapy with cyclosporine, is proposed in the HLH-94 protocol as the mainstay of treatment. It is suggested that HLH should be suspected in patients with laboratory signs of liver injury following COVID-19 infection, especially in patients with high-grade fever and a history of rheumatic conditions.